Deciduoid mesothelioma of the thorax: A comprehensive review of the scientific literature. (6th January 2017) - Paliogiannis, Panagiotis; Putzu, Carlo; Ginesu, Giorgio Carlo; Cossu, Maria Laura; Feo, Claudio Francesco; Attene, Federico; Scognamillo, Fabrizio; Nonnis, Rita; Cossu, Antonio; Palmieri, Giuseppe; Pirina, Pietro; Fois, Alessandro
Abstract: Objective: Deciduoid mesothelioma is a rare variant of malignant epithelioid mesothelioma. It often involves the peritoneum, but also thoracic cases have been reported. The aim of the present review is to describe the demographic, clinical, radiological, and pathological features of such a rare variant of thoracic mesothelioma, and the state of the art regarding the therapeutic approaches currently available. Data source: English‐language articles published from 1985 to June 2016, and related to thoracic deciduoid mesothelioma cases were retrieved using the Pubmed database. Study selection: The search terms were "mesothelioma, " "thoracic mesothelioma, " "epithelial mesothelioma, " "pleural mesothelioma, " and "deciduoid mesothelioma." Results: Forty‐four cases included in 16 articles, published in the period under investigation, were analyzed in detail. Conclusions: The mean age of the patients was 63 years, and the male to female ratio 1.7:1. Approximately 58% had exposure to asbestos, and 73% had a smoking history; familiarity was rarely reported. The most common anatomical site of origin was the right pleura, and the most frequent clinical manifestations were chest pain, dyspnea, cough, and weight loss. Thoracic X‐ray and computed tomography were the imaging techniques most employed for diagnosis and surgical planning. The pathological diagnosis was obtained by examination of surgical or biopsy specimens in most cases. The best treatment strategy of deciduoid mesothelioma is a matter of debate; nevertheless a multidisciplinary approach is currently the best option for the choice of the adequate therapeutic scheme.